Viral Transmission and Clinical Features in Asymptomatic Carriers of SARS-CoV-2 in Wuhan, China - Tan, Fen; Wang, Kaige; Liu, Jiasheng; Liu, Dan; Luo, Jianfei; Zhou, Rui (Frontiers in Medicine, 2020)
We report the clinical characteristics of, viral shedding duration in and contact tracing for asymptomatic carriers of SARS-CoV-2 in Wuhan, China. The asymptomatic carriers were relatively young (median age: 34.5 years). Chest computed tomography showed no abnormalities. The nasopharyngeal swab was optimum specimen for RNA testing. The median viral shedding duration was 11.5 days. Notably, two months of viral shedding duration we reported in two nurses was much longer than previously reported or usually we thought. The transmissibility of SARS-CoV-2 by asymptomatic carriers during the studied period in Wuhan appeared to be weak. Only one patient (1/12) was found to have transmitted the virus to the contact person. Early asymptomatic carrier detection, isolation, and contact tracing could be useful to mitigate the spread of the disease.